Estimation of the Ideal Lumbar Lordosis to Be Restored From Spinal Fusion Surgery. Issue 13 (1st July 2015) - Xu, Leilei; Qin, Xiaodong; Zhang, Wen; Qiao, Jun; Liu, Zhen; Zhu, Zezhang; Qiu, Yong; Qian, Bang-ping
<x xml:space="preserve">Abstract</x> Study Design. A prospective, cross-sectional study. Objective. To determine the independent variables associated with lumbar lordosis (LL) and to establish the predictive formula of ideal LL in Chinese population. Summary of Background Data. Several formulas have been established in Caucasians to estimate the ideal LL to be restored for lumbar fusion surgery. However, there is still a lack of knowledge concerning the establishment of such predictive formula in Chinese population. Methods. A total of 296 asymptomatic Chinese adults were prospectively recruited. The relationships between LL and variables including pelvic incidence (PI), age, sex, and body mass index were investigated to determine the independent factors that could be used to establish the predictive formula. For the validation of the current formula, other 4 reported predictive formulas were included. The absolute value of the gap between the actual LL and the ideal LL yielded by these formulas was calculated and then compared between the 4 reported formulas and the current one to determine its reliability in predicting the ideal LL. Results. The logistic regression analysis showed that there were significant associations of LL with PI and age (R = 0.508, P < 0.001 for PI; R = 0.088, P = 0.03 for age). The formula was, therefore, established as follows: LL = 0.508 × PI − 0.088 × Age + 28.6. When applying our formula to these subjects, the gap between the predicted ideal LL and the actual LL was averaged 3.9 ± 2.1°, which was significantly lower than that of the other 4 formulas. Conclusion. The calculation formula derived in this study can provide a more accurate prediction of the LL for the Chinese population, which could be used as a tool for decision making to restore the LL in lumbar corrective surgery. Level of Evidence: 3